Structural, electronic and optical properties of non-compensated and compensated models of yttrium stabilized zirconia. (4th December 2017) - Gul, Sahar Ramin; Khan, Matiullah; Yi, Zeng; Wu, Bo
Abstract: Calculations based on density functional theory (DFT) are performed to reveal the interplay between the yttrium dopant and oxygen vacancy in the structure of zirconia. Non-compensated and compensated yttrium stabilized zirconia (YSZ) systems are introduced. Oxygen deficient ZrO2 models are also simulated to investigate the influence of oxygen vacancy on the structure and optoelectronic properties of the system. Comparing the structure of different models, the compensated YSZ systems provided better structure stability. Charge compensation is very crucial for stabilizing the structure of ZrO2 . Different compensated YSZ models are introduced and their structural, electronic and optical properties are compared. The compensated YSZ system having two Y 3+ atoms at Zr 4+ sites along with one oxygen vacancy (named as Zr14 Y2 O31 ) provided very clear band gap. Very slight change in the optical response of Zr14 Y2 O31 is found compared to pure zirconia. It is concluded that not only yttrium dopant nor oxygen vacancy is only responsible for the structure stability of ZrO2 . The synergistic effect due to yttrium dopant and oxygen vacancy leads to the improved stability, suitable band structure and non-modified optical response of zirconia.